Re-Living Suspense: Emotional and Cognitive Responses During Repeated Exposure to Suspenseful Film - Chun, Changui; Park, Byungho; Shi, Chungkon (Frontiers in Psychology, 2020)
Arguments about the effects of repeated exposure to a suspenseful narrative raise controversial disputes over the paradox of suspense. The lexical meaning and theoretical analyses of suspense imply that suspense cannot be experienced repeatedly because, in such cases, the knowledge from prior viewings and the resolution of outcome will eliminate tension and suspense. However, previous studies have argued that suspense can be re-experienced even when the participants know the outcome or repeatedly confront a suspenseful narrative. This study investigated the effects of repeated exposure to a suspenseful film by collecting self-reported questionnaires and measuring psychophysiological responses. The participants (N = 50) watched clips of a suspenseful film three times and answered self-reported items regarding suspense, arousal, and enjoyment. Psychophysiological data, including skin conductance level (SCL) and electrocardiogram (ECG), were collected while the participants watched the video clips. It was hypothesized that self-reported suspense, arousal, and enjoyment as well as the physiological indices of arousal (SCL) and attention (ECG) would decrease upon repeated viewing of suspenseful clips. Furthermore, it was postulated that there would be inter-group differences depending on the awareness of potential or definite change in outcome at the end of repeatedly shown suspenseful events. The results showed that self-reported suspense and arousal, as well as physiological measures of SCL, declined with repeated exposure, although there were no significant differences on self-reported enjoyment. No group difference was found in self-reported items, but meaningful significant changes were observed in the group comparison of SCL and ECG. The findings suggest that repeated exposure to suspenseful films could result in affective habituation or desensitization to repeated stimuli. The implications and limitations of the current study and suggestions for future research are discussed.